THE EFFECT OF PROFITABILITY AND LEVERAGE ON THE TIMELINESS OF FINANCIAL REPORTING - Selvy Anggraini; Afrizal Nilwan (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
Punctuality is an important trait that shows the ability of the organization to compile and present financial statements according to the grace period, because information in financial reporting that is in accordance with the deadline is more useful for stock investors when making investment decisions. The purpose of this study is to evaluate how profitability and leverage affect the timeliness of financial statements. In this study, profitability is assessed through return on assets (ROA) and leverage is analyzed using debt to equity ratio (DER). This type of study is a quantitative set that utilizes secondary information in the form of financial statements per year from the company obtained through the www.idx.co.id site. Participants in this study are property and real estate sub-sector business entities listed on the Indonesia Stock Exchange for the period 2020-2022. The respondents of this study were 69 organizations that met 4 respondent requirements using purposive sampling techniques. The test was carried out through the use of logistic regression analysis with SPSS software version 18. The partial presumptive test output shows that profitability and leverage have a significant positive impact on the timeliness of financial statements. The findings of the coefficient of determination test explain that the percentage of the influence of profitability and leverage for the timeliness of financial statements is 10.2% and the remaining 89.8% is impacted by other independent elements that have not been studied in this study